Effect of change of boundary conditions on the screw flow characteristic - Steller, R. (Polimery, 2022)
Effect of change of boundary conditions on flow characteristic of viscous liquids in screw channel was analyzed theoretically. Two extreme variants of boundary conditions were assumed: rotating barrel and stationary screw (A) or rotating screw and stationary barrel (B). The analyses were performed for the flat, cylindrical or helical channel models using rectangular, cylindrical or helical coordinates, respectively (Fig. 1). In the case of Newtonian liquids it was shown that the solutions for any channel shape and corresponding to both variants of boundary conditions differ only in terms describing the solid body rotation. So both variants are equivalent i.e. the liquid displacement in relation to the screw surface, determining the output, is independent of the choice of boundary conditions. In case of the flow of non-Newtonian fluids in the flat channel (neglecting the real channel curvature), however, there are some differences in flow characteristics dependent on the boundary conditions’ choice. For cylindrical or helical channels (taking into consideration the channel curvature) such differences do not appear.